From the bathtub to water tank: the political relationship of reenactment in Susanne Linke and Giselda Fernandes (Urdimento: Revista de Estudos em Artes Cênicas, 2026)
The article presents an analysis of performances in relation to the practices of reenactment and cultural translation in dance, drawing on the dialogue between the solo Im Bade Wannen (1980), by German choreographer Susanne Linke, and the works Castelo D’água (2002) and Ô Água! (2002), by the Brazilian company Os Dois Cia de Dança. It investigated how the impossibility of a literal restaging triggered an aesthetic and theoretical act of disobedience. The discussion focused on how the material displacement of the work into the urban space consolidated the concept of the object-partner as a fundamental methodological operator. The study concluded that the reconfigurations examined reject the colonial copy, affirming reenactment as a living, anachronistic archive that renegotiates dance historiography through the political urgencies of the present.
Keywords: dance reenactment; living archive; object-partner; provincializing reenactment; choreopolitics